The uremic toxin indoxyl sulfate interferes with iron metabolism by regulating hepcidin in chronic kidney disease. Issue 4 (23rd August 2017) - Hamano, Hirofumi; Ikeda, Yasumasa; Watanabe, Hiroaki; Horinouchi, Yuya; Izawa-Ishizawa, Yuki; Imanishi, Masaki; Zamami, Yoshito; Takechi, Kenshi; Miyamoto, Licht; Ishizawa, Keisuke; Tsuchiya, Koichiro; Tamaki, Toshiaki
Abstract: Background: Hepcidin secreted by hepatocytes is a key regulator of iron metabolism throughout the body. Hepcidin concentrations are increased in chronic kidney disease (CKD), contributing to abnormalities in iron metabolism. Levels of indoxyl sulfate (IS), a uremic toxin, are also elevated in CKD. However, the effect of IS accumulation on iron metabolism remains unclear. Methods: We used HepG2 cells to determine the mechanism by which IS regulates hepcidin concentrations. We also used a mouse model of adenine-induced CKD. The CKD mice were divided into two groups: one was treated using AST-120 and the other received no treatment. We examined control mice, CKD mice, CKD mice treated using AST-120 and mice treated with IS via drinking water. Results: In the in vitro experiments using HepG2 cells, IS increased hepcidin expression in a dose-dependent manner. Silencing of the aryl hydrocarbon receptor (AhR) inhibited IS-induced hepcidin expression. Furthermore, IS induced oxidative stress and antioxidant drugs diminished IS-induced hepcidin expression. Adenine-induced CKD mice demonstrated an increase in hepcidin concentrations; this increase was reduced by AST-120, an oral adsorbent of the uremic toxin. CKD mice showed renal anemia, decreased plasma iron concentration, increased plasma ferritin and increased iron content in the spleen. Ferroportin was decreased in the duodenum and increased in the spleen. These changes were ameliorated by AST-120 treatment. Mice treated by direct IS administration showed hepatic hepcidin upregulation. Conclusions: IS affects iron metabolism in CKD by participating in hepcidin regulation via pathways that depend on AhR and oxidative stress.